Application of the Mudharabah Contract in Sharia Microfinancing in Rural Areas - Yudiyanto, Mohamad; Hasanudin; Gustaman; Alfiah, Mila (DPPM Universitas Pelita Bangsa, 2023)
Microfinance is an important solution to overcome economic problems in rural areas. Microfinance offers small loans to individuals or groups that do not have access to conventional financial services. This study aims to analyze the application of mudharabah contracts in Sharia microfinance in rural areas. The research method used is library research with a qualitative approach. The results of the study show that the mudharabah contract provides access to capital to rural communities who often experience limitations in obtaining financing from conventional financial institutions. With capital support and profit-sharing principles, micro enterprises in rural areas can develop, create jobs, and increase people's incomes. The implementation of mudharabah contracts in sharia microfinance in rural areas has great potential to encourage local economic growth and improve community welfare. By addressing existing challenges through the right strategies, the program can be successful and sustainable, providing significant benefits to rural communities by sharia principles. Support from various parties, including the government, Islamic financial institutions, and the public, is urgently needed to achieve this goal.